Synthesis of polyglycerol mediated covalent construction of a core‐satellite superparamagnetic mesoporous carbon nanocomposite: application on dye adsorption. Issue 9 (16th April 2018) - Yang, Xiaoxin; Li, Anxia; Wang, Wenlong; Zhang, Chuang; Wang, Jie; Yu, Binglong; Cai, Xiulan
Abstract: BACKGROUND: In this work, we used a polyglycerol (PG) mediated covalent linkage to produce a core‐satellite superparamagnetic nanocomposite, termed MMCN composed of superparamagnetic iron oxide nanoparticles (SPIONs) covalently bound to core mesoporous carbon nanoparticle (MCN). Magnetic separation is a very useful method for removing and recycling pollutant in the water by applying external magnetic field. SPIONs were good candidates that guide the MCN to desired sites using a magnet to achieve water purification. This method was used as an adsorbent for removal of methylene blue (MB) from aqueous solutions. RESULTS: The magnetism of the MMCN nanocomposites was sufficient to be magnetically separated by applying a magnetic field. The MMCN was found to be a sufficient dye adsorbent with a maximum adsorption capacity of 250 mg g −1 . Furthermore, the adsorbent could be regenerated and reused effectively by ethanol solution and allowed the treatment of wastewater contamination by MB in industry. CONCLUSION: The MMCN nanocomposites obtained high dispersibility, superparamagnetic and good recyclability through PG mediated covalent linkage. The optical properties of these multifunctional nanocomposites indicate that they can be used for highly efficient removal of water pollutants such as dyes, that can be quickly separated by applying a magnetic field. © 2018 Society of Chemical Industry